Forest and land fires, toxic haze and local politics in Indonesia. (1st December 2019) - Purnomo, H.; Okarda, B.; Shantiko, B.; Achdiawan, R.; Dermawan, A.; Kartodihardjo, H.; Dewayani, A.A.
Forest and land fires are among the major catastrophic events that occur in Indonesia. They are a major cause of deforestation and greenhouse gas emissions. Their multiple sources are most diverse and root in nature and society. The immediate fire effects directly and the long-term landscape ecosystem degradations indirectly cause major and persisting and serious problems of public health and ecosystem service. Smoke haze from the forest and land fires in Sumatra and Kalimantan in 2015 caused significant environmental and economic losses in Indonesia, Singapore and Malaysia. We describe the different types of land uses and land cover where fires and smoke haze took place, and how local politics have affected fire use from 2001 to 2017. We calculated hot spots from satellite imageries as proxies for fire occurrences and applied regression analysis to understand the link between fire and local politics in Sumatra and Kalimantan. The results show that the greatest frequency of hot spots occurred in wood and oil palm plantations and logging concessions (47%), followed by conservation areas (31%) and community land (22%). Local elections involve land transactions, and fires were used as a cheap way to increase the land value. The use of fire as means of land clearing was strongly influenced by local politics. Their frequency and abundance obviously increased about a year prior to local elections. The reasons behind the correlation need to be understood so that appropriate incentives and sanctions can be put in place and deter political leaders from using fire as an incentive to their advantage.